ANALISIS PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO, KECIL DAN MENENGAH PADA UMKM DI KECAMATAN TIROANG KABUPATEN PINRANG - Janna, Harisatul; Tikollah, M Ridwan; Dunakhir, Samirah (Universitas Jabal Ghafur, 2024)
This study aims: to analyze how the level of suitability of the preparation of MSME financial statements in Tiroang District and Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). The variable of this study is the analysis of the preparation of financial statements based on Micro, Small and Medium Financial Accounting Standards in Tiroang District, Pinrang Regency. The population of this study was MSMEs in Tiroang District, Pinrang Regency registered in the Cooperative Office and MSMEs of Pinrang Regency totaling 40 MSMEs, while the sample amounted to 12 MSMEs taken using purposive sampling techniques. Data collection is carried out using documentation techniques. Data analysis was performed using a comparative descriptive analysis model. The results of this study show that the level of suitability for the preparation of MSME financial statements in Tiroang District is only 9%, with inappropriate qualifications.